Planisphère sur la projection de Mercator: Planisphere - Brué, Adrien-Hubert, 1786-1832 (Cartographer); Levasseur, Émile, 1828-1911 (Cartographer)
World map centered around the Bering Strait. Includes weather details like currents, snow patterns, and ice. Details likely for sailing purposes. Relief shown by hachures. Includes notes about when northern areas were last visited, with 1872 as the most recent date. Atlas Universel De Geographie Physique, Politique, Ancienne Et Moderne, Contenant Les Cartes Generales Et Particulieres De Toutes Les Parties Du Monde . Dresse par A. Brue, Geographe. Nouvelle Edition Revue Par E. Levasseur . Comprenant 66 Cartes Et 85 Cartouches Tenant Lieu D'Autant De Cartes. Institut Geographique De Paris. Charles Delagrave, Editeur De La Societe De Geographie De Paris, 58, Rue Des Ecoles, 58. 1875 Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .